2016
DOI: 10.17058/cinergis.v17i3.8118
|View full text |Cite
|
Sign up to set email alerts
|

Uso de psicotropicos pelo enfermeiro: sua relação com o trabalho

Abstract: Exceto onde especificado diferentemente, a matéria publicada neste periódico é licenciada sob forma de uma licença Creative Commons -Atribuição 4. INTRODUÇÃOO trabalho é considerado uma atividade de sobrevivência, pois de modo simples e concreto é a forma mais complexa da expressividade do ser humano; sendo assim, uma necessidade de expressão que envolve a busca de seu espaço.1 Todo e qualquer trabalho pode trazer, tanto a satisfação, ao trabalhador como também promover descontentamento social, pessoal, monot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
12

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
0
3
0
12
Order By: Relevance
“…É preciso levar em consideração as singularidades de cada localidade, no sentido da oferta possível e assertiva dos cuidados em saúde mental. É sabido que a enfermagem trabalha em um certo limite de disponibilidade psíquica, com uso frequente de medicação controlada, e um evento como esta pandemia tem poder de disparar crises até quiçá controladas 25 . Estudo recente sugere a definição de uma estrutura para a construção de intervenções relacionadas à saúde mental com três pontos principais: 1.…”
Section: Introductionunclassified
“…É preciso levar em consideração as singularidades de cada localidade, no sentido da oferta possível e assertiva dos cuidados em saúde mental. É sabido que a enfermagem trabalha em um certo limite de disponibilidade psíquica, com uso frequente de medicação controlada, e um evento como esta pandemia tem poder de disparar crises até quiçá controladas 25 . Estudo recente sugere a definição de uma estrutura para a construção de intervenções relacionadas à saúde mental com três pontos principais: 1.…”
Section: Introductionunclassified
“…The working conditions of the nursing team, especially in hospitals, have been considered improper, becoming health risk generators, forming a set of problems that encompasses inadequate remuneration, accumulation of service schedules, increase in the continuous workload in shifts, and tensiogenic characteristics of the health services, both by the nature of the care provided to people at risk, and by the social division of work. [5][6] Due to these disorders, these professionals are affected by several symptoms and diseases, of the most varied forms and origins, such as: arterial hypertension, cardiovascular diseases, alcoholism, stress, and musculoskeletal disorders related to work, in addition to anguish and depression that cause harms to the body and mind of the nurses, impairing the work capacity of these professionals. 7 Given these factors, nursing is one of the professional classes most susceptible to the consumption of psychoactive substances (PASs), because these are historically related as ways to relieve tension and reduce the stress caused by work.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, a study showed that of the 86 health workers, 17.4% of participants had signs suggestive of mild depression, 10.5% moderate and 12.8% severe, with 70.9% of these professionals not using any medication, while the other 20.1% mentioned consumption of psychoactive drugs as anxiolytics and antidepressants (29) . Characteristics about the health status of these professionals were also reported in studies investigating factors and reasons that led health care professionals to start consuming PASs, which revealed that workers pointed out several signs and symptoms in relation to their health such as depression, anxiety, stress, insomnia, mental exhaustion, physical fatigue and pain, turning to substances such as antidepressants, anxiolytics, opioids and alcohol to relieve such symptoms (6)(7)26,29,35) .…”
Section: Discussionmentioning
confidence: 99%
“…These workers can perceive situations that occur in the work environment as being common to the profession, that is, as factors inherent to the profession, but that lead them to create defense strategies to deal with the risks and to maintain their mental health. Even becoming part of the work, they are exposed to mental, physical and emotional illness due to the relationship between work and health (7,35) . From this perspective, a study showed that of the 86 health workers, 17.4% of participants had signs suggestive of mild depression, 10.5% moderate and 12.8% severe, with 70.9% of these professionals not using any medication, while the other 20.1% mentioned consumption of psychoactive drugs as anxiolytics and antidepressants (29) .…”
Section: Discussionmentioning
confidence: 99%